Pancasila sebagai Jiwa Persatuan dalam Membangun Moderasi Beragama di Indonesia - Dominikus Doni Ola; Megawati Naibaho (Prosiding Seminar Nasional Ilmu Pendidikan Agama dan Filsafat, 2024)
Pancasila is a legacy of our ancestors and has very noble values. Nobility is contained in the five principles of Pancasila as a noble "legacy", especially for building religious moderation in Indonesia. The researchers are interested in exploring the values contained in Pancasila in order to maintain the mandate of the founders of the Indonesian nation. On the other hand, the author admits that the knowledge and appreciation of some citizens of the Republic of Indonesia (WNRI) are starting to fade. This can be seen in the lack of appreciation and respect for others, especially those of different religions, cultures, races, and groups. This is a concern and a threat to the unity of Indonesian daughters and sons. This research was conducted using the library research method. By digging up information from main and supporting sources as well as reliable references, the researcher wants to present data and offer an idea to return to living up to the values contained in Pancasila. Indonesian people should be proud to have Pancasila as a democratic state philosophy. The Pancasila philosophy needs to be lived in a spirit of honesty, justice, solidarity and openness. This guarantees the realization of a peaceful and prosperous life. Thus, Pancasila is the spirit of unity in building religious moderation in Indonesia. This will guarantee protection for every citizen in all aspects of life, especially religious freedom.